EVALUATION OF ORALLY DISINTEGRATING TABLET OF IBUPROFEN-β-CYCLODEXTRIN INCLUSION COMPLEX - PURNAMASARI, NUR AINI DEWI; SAPUTRA, PRATAMA ANGGI (International Journal of Applied Pharmaceutics, 2020)
Objective: This study aims to determine the effect of the inclusion complex formation of ibuprofen (IB) with β-cyclodextrin (β-CD) in improving water solubility and taste masking as well as to study the effect of the combined use of super disintegrants in IB-β-CD ODT (Orally disintegrating tablet). Methods: IB-β-CD inclusion complex was prepared by spray drying technique with a 1:1 molar ratio. ODTs were prepared by the direct compression method using various ratios of Ac-Di-Sol® and Kollidon® CL as super disintegrant. The inclusion complex was characterized using spectroscopy FT-IR (Fourier-transform infrared) and DSC (Differential Scanning Calorimetry). The physical properties and dissolution rate of ODTs were evaluated. Dissolved drug concentration at 60 min (Q60) and Dissolution Efficiency (DE60) was calculated using the dissolution test result. Results: The unpleasant taste of IB had been successfully masked by IB-β-CD. Formula 1 was observed having 14.5 sec of disintegration, fastest compared to the other formulas. Moreover DE60 value of formula I was higher than the other formulas (113.45). Conclusion: IB-β-CD Inclusion complex prepared by spray drying method (1: 1) increased the water solubility and masked the unpleasant taste compared to IB moreover combination of Ac-Di-Sol® and Kollidon® CL increased ODT dissolution rate.